Monocrystalline structure formation of doped perfect silicon crystals - Azarenkov, N.А.; Semenenko, V.Е.; Ovcharenko, А.I.; Pylypenko, M.M. (Вопросы атомной науки и техники, 2016)
In this paper we consider perfect doped silicon single crystals growth. Special features of anodic etching of n- and p-type single crystals has been revealed. An impact of seed orientation on dislocation and defect structure evolution in crystal on different growth stages has been found. Influence of heat treatment on phase-structural condition of single crystals and nonequilibrium carrier lifetime has been determined. Вивчено особливості вирощування досконалих легованих монокристалів кремнію. Виявлено особливості анодного травлення монокристалів n- і p-типів. Визначено вплив орієнтації запалу на еволюцію дислокаційної і дефектної структур у кристалі на різних стадіях росту. Встановлено вплив термообробки на структурно-фазовий стан монокристалів і час життя нерівноважних носіїв струму. Изучены особенности выращивания совершенных легированных монокристаллов кремния. Выявлены особенности анодного травления монокристаллов n- и p-типов. Определено влияние ориентации затравок на эволюцию дислокационной и дефектной структур в кристалле на различных стадиях роста. Установлено влияние термообработки на структурно-фазовое состояние монокристаллов и время жизни неравновесных носителей тока.